2017
DOI: 10.1080/19336934.2017.1402993
|View full text |Cite
|
Sign up to set email alerts
|

Extendingjulius seizure, a bang-sensitive gene, as a model for studying epileptogenesis: Cold shock, and a new insertional mutation

Abstract: The bang-sensitive (BS) mutants of Drosophila are an important model for studying epilepsy. We recently identified a novel BS locus, julius seizure (jus), encoding a protein containing two transmembrane domains and an extracellular cysteine-rich loop. We also determined that jus, a previously identified BS mutation, is an allele of jus by recombination, deficiency mapping, complementation testing, and genetic rescue. RNAi knockdown revealed that jus expression is important in cholinergic neurons and that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Mutations in 1,200 Drosophila genes have been registered as associated with heat sensitivity. Increasing the temperature of ectothermal animals increases the temperature of the central nervous system and induces the stereotypic seizure response in sensitized genetic models 21 , 33 35 , 47 . Surprisingly few (~30%) of the genes that can mutate to produce mechanically induced phenotypes co-occur with those that are temperature dependent.…”
Section: Epilepsy Modeling In Drosophilamentioning
confidence: 99%
“…Mutations in 1,200 Drosophila genes have been registered as associated with heat sensitivity. Increasing the temperature of ectothermal animals increases the temperature of the central nervous system and induces the stereotypic seizure response in sensitized genetic models 21 , 33 35 , 47 . Surprisingly few (~30%) of the genes that can mutate to produce mechanically induced phenotypes co-occur with those that are temperature dependent.…”
Section: Epilepsy Modeling In Drosophilamentioning
confidence: 99%
“…For RNAi knockdown of jus expression, the following jus enhancer GAL4 lines were used (described in Pfeiffer et al, 2008): 55F051 (BL# 39124), 55G02 (BL# 46070; no longer available from BDSC but see Horne et al, 2017 and Dean et al, 2018), 59D01 (BL# 46416) and 90B09 (this paper). Each of these jus -GAL4 lines was crossed to the UAS- jus RNAi line P{y[+t7.7] v[+t1.8]=TRiP.JF03192}attP2 (BL#28764; Ni et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Previous work demonstrated that using the 55G02-GAL4 line to drive expression of a wildtype jus transgene could effectively rescue the bang sensitive phenotype of a mutant jus allele (Horne et al, 2018). However, this rescue was not complete, and later it was found that overlap of 55G02-GAL4 expression with endogenous Jus expression was limited (Dean et al, 2018). These findings suggested that 55G02 may not be the most effective enhancer to manipulate gene expression in the Jus-expressing neurons that affect bang-sensitivity.…”
Section: Identifying a More Specific Gal4mentioning
confidence: 99%
See 2 more Smart Citations